Copper-nickel-modified Boron-doped Diamond Electrode for CO2 Electrochemical Reduction Application: A Preliminary Study - Jiwanti, Prastika Krisma; Aritonang, Rani Puspitasari; Abdullah, Imam; Einaga, Yasuaki; Ivandini, Tribidasari Anggraningrum (Makara Journal of Science, 2019)
CO2 electrochemical reduction (CO2ER) activity is known to be influenced by electrode materials. In this study, we report the fabrication of a copper-nickel-modified boron-doped diamond (CuNi-BDD) electrode using wet chemical seeding and electrodeposition. Annealing was performed to improve the stability of the modified electrode during elec-trolysis. Characterization of the modified BDD electrodes shows successful deposition without damage to the surface of the BDD support material. CO2ER was conducted with the CuNi-BDD electrode, which produces various important products including methanol, formic acid, CO, and CH4. Additionally, a different applied potential affected the product distribution. CO2ER was also conducted on the surfaces of Cu-BDD and Ni-BDD electrodes for comparison.